Given "w = 8 \\ lb., L = 3 \\ in. = \\frac{3}{12} feet = \\frac{1}{4} feet" , "\\gamma = 2 \\ lbs\/feet" .
"u(0 ) = 0, u'(0) = 2 \\ in\/s = \\frac{1}{6} feet\/s".
Now, differential equation is "mu'' + \\gamma u' + ku = 0 : u(0)=0,u'(0) = \\frac{1}{6}"
where "m = \\frac{w}{g} = \\frac{1}{4} \\ lbs^2\/feet, k = \\frac{w}{L} = 32 \\ lb\/feet" .
"\\implies \\frac{1}{4}u''+2u'+32u = 0 :u(0)=0,u'(0)=\\frac{1}{6}"
"\\implies u''+8u'+128u = 0"
"\\implies D = \\frac{-8\\pm \\sqrt{64-512}}{2} = -4\\pm i \\sqrt{112}" where D "= \\frac{d}{dt}"
Hence, "u = e^{-4t} (c_1 cos(\\sqrt{112}t)+c_2 sin(\\sqrt{112}t))" .
Now using "u(0)=0 \\implies c_1 = 0" .
So, "u = c_2 e^{-4t} sin(\\sqrt{112}t)"
Now, "u'(0)=\\frac{1}{6} \\implies \\frac{1}{6} = c_2 (-4)(\\sqrt{112}) \\implies c_2 = -\\frac{1}{24\\sqrt{112}}"
Hence, "u(t) = -\\frac{1}{24\\sqrt{112}} e^{-4t} sin(\\sqrt{112} \\ t)"
Comments
Leave a comment